Kebijakan Pemerintah terhadap Tapera di Indonesia; Analisis Prinsip Ekonomi Syariah - Ulfanur, Maulina; Asysyura, Asysyura; Isra, Marzuti; Eryani, Eryani (State of Islamic Institute Langsa, 2024)
Ideally, the TAPERA policy in Indonesia is designed to help the public, particularly workers, own decent housing through a systematic housing savings program. However, in reality, many people do not fully understand this program and question its implementation, especially regarding its alignment with the principles of Islamic economics. The purpose of this study is to analyze the government's policy on TAPERA in Indonesia and examine its application from the perspective of Islamic economic principles. This article falls under literature research with a qualitative approach, using normative legal studies methodology, explained with descriptive analysis. In conclusion, the Indonesian government's policy on TAPERA aims to improve access to decent and equitable housing for the public, especially those with limited income, while reducing social disparities. From the perspective of Islamic economics, TAPERA applies the principles of justice, maslahat, ta'awun, and balance, offering interest-free financing and focusing on more sustainable social welfare.